Anticipated emotional solidarity, emotional reasoning, and travel intention: A comparison of two destination image models. (March 2023) - Joo, Dongoh; Cho, Heetae; Woosnam, Kyle Maurice
Abstract: Looking at potential faith-based tourists, this study examined how their anticipation of emotional solidarity influenced the cognitive and affective images of their preferred destination, which in turn led to travel intention. To see if potential tourists lacking first-hand experiences of the destination engaged in emotional reasoning, Model 1 (cognitive destination image → affective destination image) was compared with Model 2 hypothesizing the opposite. Results from both models supported the positive impacts of anticipated emotional solidarity in formulating favorable destination images and promoting travel intention. Notably, in Model 2, affective destination image successfully predicted cognitive destination image, suggesting the possibility of emotional reasoning. Collectively, the findings supported the practical value of putting social emotions at the forefront of destination marketing to attract potential tourists. . Highlights: Model 1 tested if cognitive image antecedes affective image and travel intention. Model 2 tested if affective images antecede cognitive image and travel intention. Anticipation of emotional solidarity promoted destination images in both models. Models 1 and 2 showed similar model fit and explanatory power. Model 2 results allowed more logical interpretation.